AN OVERVIEW OF MULTIFACETED SIGNIFICANCE OF EUDRAGIT POLYMERS IN DRUG DELIVERY SYSTEMS - Singh, Sukhbir; Neelam, .; Arora, Sandeep; Singla, Yashpal (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Polymers constitute the major part of pharmaceutical formulations functionality and significance. Development of novel drug delivery system (NDDS) has been made possible by eudragit polymers to modify the release pattern of drug. The basic objective of sustained drug release is to achieve more effective therapies by eliminating potential for both under and overdosing. Other advantages include maintenance of drug concentration with in desired range, fewer administration, optimal drug use and patient compliance. This review article gives outline of classification, nomenclature, physiological, and pharmaceutical properties of eudragit polymers. Eudragit polymers can be classified on the basis of use or type of formulation produced and includes time-controlled drug release by sustained release formulations, gastro-resistance and GI targeting by enteric formulations and moisture protection and odor/taste masking by protective formulations. Eudragit polymers are available in wide range of physical forms viz. aqueous dispersion, organic solution, granule and powder with varying degrees of solubility. Eudragit polymers have numerous drug release mechanism and wide applications in different drug delivery systems i.e. ophthalmic, buccal, sublingual, enteric, oral, colon, vaccine, gene, vaginal and transdermal drug delivery. It has been concluded that eudragit polymers have multifaceted applications in pharmacy and drug delivery system. Keywords: Eudragit, Time-controlled, Sublingual.